International comparison of spending and utilization at the end of life for hip fracture patients. (7th September 2021) - Blankart, Carl Rudolf; van Gool, Kees; Papanicolas, Irene; Bernal‐Delgado, Enrique; Bowden, Nicholas; Estupiñán‐Romero, Francisco; Gauld, Robin; Knight, Hannah; Abiona, Olukorede; Riley, Kristen; Schoenfeld, Andrew J.; Shatrov, Kosta; et al.
Abstract: Objective: To identify and explore differences in spending and utilization of key health services at the end of life among hip fracture patients across seven developed countries. Data Sources: Individual‐level claims data from the inpatient and outpatient health care sectors compiled by the International Collaborative on Costs, Outcomes, and Needs in Care (ICCONIC). Study Design: We retrospectively analyzed utilization and spending from acute hospital care, emergency department, outpatient primary care and specialty physician visits, and outpatient drugs. Patterns of spending and utilization were compared in the last 30, 90, and 180 days across Australia, Canada, England, Germany, New Zealand, Spain, and the United States. We employed linear regression models to measure age‐ and sex‐specific effects within and across countries. In addition, we analyzed hospital‐centricity, that is, the days spent in hospital and site of death. Data Collection/Extraction Methods: We identified patients who sustained a hip fracture in 2016 and died within 12 months from date of admission. Principal Findings: Resource use, costs, and the proportion of deaths in hospital showed large variability being high in England and Spain, while low in New Zealand. Days in hospital significantly decreased with increasing age in Canada, Germany, Spain, and the United States. Hospital spending near date of death was significantly lower for women in Canada, Germany, and the United States. The age gradient and the sex effect were less pronounced in utilization and spending of emergency care, outpatient care, and drugs. Conclusions: Across seven countries, we find important variations in end‐of‐life care for patients who sustained a hip fracture, with some differences explained by sex and age. Our work sheds important insights that may help ongoing health policy discussions on equity, efficiency, and reimbursement in health care systems.